Youth participatory action research and school improvement: The missing voices of black youth in Montreal - Livingstone, Anne-Marie; Celemencki, Jacqueline; Calixte, Melissa (Canadian Journal of Education/Revue canadienne de l'éducation, 2014)
The article discusses the implementation and results of a youth participatory action research (YPAR) project carried out with black high school students in 2009 and 2010 in Montreal, QC. The aim of the project was to involve black youth in studying the factors that either enhance or impede their success in school and thereby have them identify solutions that would be effective in reducing the high dropout rate of black students in Montreal. The participating students were 15 to 18 years of age, attended four high schools located across the city, and thus represented the cultural and linguistic diversity of Montreal’s black community. The results demonstrate that YPAR can lead to a deeper and fuller understanding of the factors that shape students’ experiences and performance in school than research that ignores the voices of young people. The study shows that black youth believe academic achievement is influenced by multiple and inter-related factors, including family, peers, school, and neighbourhood. The youth contend that high schools must do more to support black students by setting high expectations for success, maintaining positive teacher–student relations, integrating multicultural curricula such as courses on black history, promoting more innovative pedagogies in the classroom, expanding the range of extra-curricular activities, and working more closely with black community organizations. Résumé Cet article présente les résultats d’un projet de recherche participative qui s’est tenu en 2009–2010 avec un groupe de jeunes élèves noirs fréquentant des écoles secondaires de Montréal (Québec). L’objectif du projet était d’impliquer des jeunes noirs dans un processus d’étude des facteurs pouvant encourager ou inhiber leur succès scolaire, et ainsi d’identifier avec eux des mesures pouvant réduire les taux de décrochage scolaire des étudiants noirs à Montréal. Les élèves recrutés pour ce projet étaient âgés de 15 à 18 ans et fréquentaient quatre écoles secondaires situées dans différents quartiers de l’île de Montréal, et ainsi représentaient bien la diversité culturelle et linguistique des communautés noires de Montréal. Les résultats démontrent que les recherches participatives impliquant des élèves peuvent mener à une compréhension plus riche et plus profonde des facteurs qui influencent les expériences et les performances scolaires des élèves que les études qui ne prennent pas en considération leurs considérations. Les résultats de notre étude démontrent que les jeunes noirs y ayant participé expliquent que la réussite scolaire est influencée par des facteurs multiples et interreliés, incluant la famille, les pairs, l’école, et la communauté environnante. Ces jeunes croient que les écoles devraient offrir plus de soutien aux étudiants noirs afin qu’ils et elles réussissent, avec des mesures telles un meilleur climat à l’école, des interrelations positives entre les étudiants et les enseignants, l’implantation d’un curriculum interculturel incluant des cours sur l’histoire des noirs, des approches pédagogiques variées et novatrices, un plus grand choix d’activités parascolaires, et des partenariats avec des organismes de la communauté noire.